All Days 2008
DOI: 10.2118/119900-ms
|View full text |Cite
|
Sign up to set email alerts
|

Critical Evaluations of Additives Used in Shale Slickwater Fracs

Abstract: Slickwater fracturing has increased over the past decade with the advent of shale gas plays. Horizontal wells are now the standard with up to 1 million gallons of water in as many as 6 to 9 frac stages per well. The objective is to create as much contact with the reservoir as possible and many times a secondary goal is to prop open the created fractures. Additive packages have been minimized to save money. Due to environmental concerns and fresh water availability, the flowback and produced water is collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…The evolvement of the fractures around the main fracture would increase the regional permeability, but it also could lead to significant leakoff, which could limit the development of hydraulic fracture. However, it is hard to determine whether these fractures are in open state and stay as viable flowpaths [47,72]. The key factor that can blunt the fracture propagation is shear sliding along the interface [28] and Anderson et al [6] found that if the frictional properties changed along the interfacial surface close to hydraulic fracture, the path of the fracture could be alerted.…”
Section: Influences Of Complex Geological Structures On Hydraulic Framentioning
confidence: 99%
“…The evolvement of the fractures around the main fracture would increase the regional permeability, but it also could lead to significant leakoff, which could limit the development of hydraulic fracture. However, it is hard to determine whether these fractures are in open state and stay as viable flowpaths [47,72]. The key factor that can blunt the fracture propagation is shear sliding along the interface [28] and Anderson et al [6] found that if the frictional properties changed along the interfacial surface close to hydraulic fracture, the path of the fracture could be alerted.…”
Section: Influences Of Complex Geological Structures On Hydraulic Framentioning
confidence: 99%
“…Resins are used near the end of the stimulation process to hold proppant in place; ceramics are used when a stronger proppant is required. Ceramics also have a lower specific gravity than sand, allowing them to remain buoyant in the slickwater (Kaufman et al, 2008). Gels are used to increase the viscosity of the water, allowing it to carry proppant more effectively, but these are not recommended for brittle shale stimulation.…”
Section: Stimulationmentioning
confidence: 99%
“…Friction reducers that are mainly polyacrylamide based serves as one of the primary additives in slickwater fracturing fluid to reduce the friction drag related to high pump rate. The friction reducer could change the turbulent flow to laminar flow by interacting with turbulent eddies, and the reduction of energy loss could reach as much as 20%e80% in laboratory experiments and 30%e90% in field applications compared with fresh water (Kaufman et al, 2008;Rimassa et al, 2009;Shah and Kamel, 2010;Sun et al, 2010;Lindsay et al, 2011;Paktinat et al, 2011). The concentration of polymer friction reducer is about 1 wt% in slickwater fracturing fluid, but a great amount of polymer would remain in microfractures after flowback considering the large volumes of fracturing fluid required in slickwater treatments (Carman and Cawiezel, 2010;Zhou et al, 2011;Sun et al, 2014).…”
Section: Introductionmentioning
confidence: 99%